THE SYLLABLE STRUCTURE IN EUROPEAN PORTUGUESE - Mateus, Maria Helena; D'Andrande, Ernesto (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
The goal of this paper is to discuss the internal structure of the syllable in European Portuguese and to propose an algorithm for base syllabification. Due to the analysis of consonant clusters in onset position and the occurrence of epenthetic vowels, and considering the variation of the vowels in word initial position that occupy the syllable nucleus without an onset at the phonetic level, we assume that, in European Portuguese, the syllable is always constituted by an onset and a rhyme even though one of these constituents (but not both) may be empty, that is, one of then may have no phonetic realisation.